Noninvasive Peripheral Arterial Diagnosis - AbuRahma, Ali F.; Bergan, John J.; SpringerLink (Online service) (London : Springer London, 2010)
"Noninvasive Peripheral Arterial Diagnosis" is the newest definitive text on the current techniques used in assessing vascular disorders. Readers will receive authoritative information and will be guided through the establishment and accreditation of a vascular laboratory and introduced to the physics of diagnostic testing. Chapters, written by selected experts, comprehensively explain the use of ultrasound in diagnosing cerebrovascular, renovascular, visceral ischemia and peripheral arterial disease as well as venous disorders and deep abdominal vascular conditions. Noninvasive Vascular Diagnosis contains over 300 illustrations, many of them in colour. Due to the special sections which give clinical correlations, this book will be invaluable to physicians who treat vascular disorders, surgeons, cardiologists, vascular radiologists and the vascular laboratory staff.
Overview of Peripheral Arterial Disease of the Lower Extremity -- Overview of Noninvasive Vascular Techniques in Peripheral Arterial Disease -- Segmental Doppler Pressures and Doppler Waveform Analysis in Peripheral Vascular Disease of the Lower Extremities -- Pulse Volume Recording in the Diagnosis of Peripheral Vascular Disease -- Duplex Scanning for Lower Extremity Arterial Disease -- Duplex Surveillance of Infrainguinal Bypass Grafts -- Rationale and Benefits of Surveillance After Prosthetic Infrainguinal Bypass Grafts -- Rationale and Benefits of Surveillance After Percutaneous Transluminal Angioplasty and Stenting of Iliac and Femoral Arteries -- Duplex Ultrasound in the Diagnosis and Treatment of Femoral Pseudoaneurysms -- Lower Extremity Arterial Mapping: Duplex Ultrasound as an Alternative to Arteriography Prior to Femoral and Popliteal Reconstruction -- Preoperative Saphenous Vein Mapping -- Noninvasive Diagnosis of Upper Extremity Vascular Disease -- Ultrasound Imaging of Upper Extremity Arteries: Clinical Applications -- Protocol and Technique of Dialysis Ultrasound Surveillance -- Noninvasive Evaluation for Congenital Arteriovenous Fistulas and Malformation -- Clinical Implications of the Vascular Laboratory in the Diagnosis of Peripheral Arterial Disease.
Keywords: Medicine; Radiology, Medical; Diagnosis, Ultrasonic; Medicine & Public Health; Ultrasound; Imaging / Radiology